2019
DOI: 10.1017/s0954102018000482
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and optimization of EPSs produced by a cold-adaptedMarinobacterisolate from Antarctic seawater

Abstract: Marinobacter sp. W1-16 from Antarctic surface seawater was analysed for the production of extracellular polymeric substances (EPSs). Enhancement of the EPS biosynthesis was carried out by evaluating the influences of the carbon source (type and concentration), temperature, pH and salinity. EPS yields varied strongly depending on sugar substrate and temperature, while pH and salinity did not strongly affect levels of EPS production. Marinobacter sp. W1-16 produced the highest quantity of EPSs when growing at 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…grown on alkane formed cell aggregates supported by enhanced EPS production (Sabirova et al, 2011). Analysis of EPS produced by Marinobacter isolates revealed high levels of carbohydrates with a broad range of structural monosaccharides (Caruso et al, 2019), including xylose (Bhaskar et al, 2005). Members of the genus Colwellia isolated from cold waters and sediments produced cryoprotectant EPS (Marx et al, 2009) as well as EPS enriched in deoxysugarcontaining polysaccharides (Casillo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…grown on alkane formed cell aggregates supported by enhanced EPS production (Sabirova et al, 2011). Analysis of EPS produced by Marinobacter isolates revealed high levels of carbohydrates with a broad range of structural monosaccharides (Caruso et al, 2019), including xylose (Bhaskar et al, 2005). Members of the genus Colwellia isolated from cold waters and sediments produced cryoprotectant EPS (Marx et al, 2009) as well as EPS enriched in deoxysugarcontaining polysaccharides (Casillo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although Marinobacter can use hydrocarbons as carbon source, various studies demonstrated that it can also grow and produce EPS on other carbon sources such as glucose. Marinobacter species have been shown to produce exopolysaccharide polymers with excellent emulsifying activity against hydrocarbons that were superior to commercial synthetic surfactants like Tween 80 (Caruso et al, 2019 ). Marinobacter sp.…”
Section: Marine Biosurfactant-producing Bacteriamentioning
confidence: 99%
“…The highest yield was produced when the culture was grown at 15°C and in the presence of 2% glucose. However, the strain was able to synthesize EPS, even at 4°C, albeit in lower quantities, suggesting that the EPS might have cryoprotective functions (Caruso et al, 2019 ). In addition, Marinobacter sp.…”
Section: Marine Biosurfactant-producing Bacteriamentioning
confidence: 99%
“…A plethora of ecological roles are played by EPSs in cold environments. Beside acting as osmoprotectants, EPSs produced by cold-adapted bacteria have been reported as ROS scavengers and cryoprotectants [ 147 , 148 , 149 , 150 ]. For example, high concentrations of EPSs are produced at low and sub-freezing temperatures by Pseudoalteromonas , Winogradskyella and Marinobacter isolates, probably acting as a diffusion barrier to solutes and a physical-like barrier to ice formation [ 148 , 149 ].…”
Section: Bacteriamentioning
confidence: 99%